2014
DOI: 10.5901/mjss.2014.v5n8p596
|View full text |Cite
|
Sign up to set email alerts
|

Townships as Crime ‘Hot-Spot’ Areas in Cape Town: Perceived Root Causes of Crime in Site B, Khayelitsha

Abstract: Crime in South Africa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Violence and other contact crimes abound within its communities. 3,4 Khayelitsha’s proportion of violent crimes, captured as crimes against a person (contact crimes), are considerably higher than the national average, and crime is also prevalent in Mitchells Plain. 24 Previous studies have shown violence to be a considerable problem within South African psychiatric centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Violence and other contact crimes abound within its communities. 3,4 Khayelitsha’s proportion of violent crimes, captured as crimes against a person (contact crimes), are considerably higher than the national average, and crime is also prevalent in Mitchells Plain. 24 Previous studies have shown violence to be a considerable problem within South African psychiatric centres.…”
Section: Discussionmentioning
confidence: 99%
“…2 The catchment area of the hospital includes two urban townships, Mitchells Plain and Khayelitsha; both of which are characterised by high levels of crime and substance use, and poor socio-economic status. 3,4 Recent data confirm that Mitchells Plain and Khayelitsha have one of the highest rates of contact crimes in the province (SAPS). 5…”
Section: Introductionmentioning
confidence: 98%
“…According to Yiftachel (2009), this violence in design is evident in most cities of the South that exhibit signs of "creeping urban apartheid" showing how the "gradations of rights and capabilities commonly based on inscribed classifications" trigger crime and violence. The South African case of the Apartheid planning systems shows how the spatial segregation has also contributed to some insecurity and safety issues in most poor suburbs that were positioned on the city edges and also with limited services such as police stations and integrated transport systems that often places the commuters at risk, especially those navigating the first/last mile in the early hours of the morning before daylight or later in the day after sunset (Breetzke, 2012;Jean-Claude, 2014). The distance from services and economic opportunities, such as schools and work forces the residents to leave homes early and come back late, compromising their safety as they navigate this last mile (Nche, 2020).…”
Section: Infrastructure Violence In Emerging Human Settlements and Th...mentioning
confidence: 99%
“…In South Africa, townships were established to provide low-cost housing for black workers so that they may live closer to their places of employment in cities and towns (Kooijmans, 2014). Today's township life is characterized by poverty, violence, and abuse, and residents' safety has been compromised (Manaliyo, 2014). Most schools are classified quintiles 1, 2, and 3 schools due to the high rate of unemployment and poverty in the townships, with parents unable to contribute to school fees due to their poor socioeconomic level.…”
Section: Introductionmentioning
confidence: 99%